2005
DOI: 10.1088/0957-4484/17/1/015
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of basic standard encryption algorithm modules using nanosized complementary metal–oxide–semiconductor–molecular circuits

Abstract: We are proposing that the recently proposed semiconductor–nanowire–molecular architecture (CMOL) is an optimum platform to realize encryption algorithms. The basic modules for the advanced encryption standard algorithm (Rijndael) have been designed using CMOL architecture. The performance of this design has been evaluated with respect to chip area and speed. It is observed that CMOL provides considerable improvement over implementation with regular CMOS architecture even with a 20% defect rate. Pseudo-optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The challenge is to implement correlationbased learning laws, such as STDP [4], based on the state of a two-terminal nanodevice for long-term potentiation (LTP) (for pre-before-postsynaptic spiking) and long-term depression (LTD) (for post-before-presynaptic spiking) as well as state storage. Conventional CMOL circuits [1,5] comprise bistable single-electron devices (SEDs) whose behavior are like single bit Resistance-change RAMs (ReRAMs). But, the resistance of recently fabricated nanodevice, 'memristive' [6], is nonlinear and varying between "On" (low resistance) state and "Off" (high resistance) state by applying appropriate voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is to implement correlationbased learning laws, such as STDP [4], based on the state of a two-terminal nanodevice for long-term potentiation (LTP) (for pre-before-postsynaptic spiking) and long-term depression (LTD) (for post-before-presynaptic spiking) as well as state storage. Conventional CMOL circuits [1,5] comprise bistable single-electron devices (SEDs) whose behavior are like single bit Resistance-change RAMs (ReRAMs). But, the resistance of recently fabricated nanodevice, 'memristive' [6], is nonlinear and varying between "On" (low resistance) state and "Off" (high resistance) state by applying appropriate voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The results implied that CMOL FPGA may provide area-delay advantage beyond two orders of magnitude over purely CMOS FPGA circuits, at manageable power consumption, simultaneously with high defect tolerance (above 20% of bad nanodevices). Later, an almost similar density advantage was reported for CMOL FPGA implementation of an advanced encryption algorithm [22]. However, these results were still insufficient to evaluate the benefits of the CMOL FPGA concept for general-purpose computing.…”
mentioning
confidence: 69%
“…Moreover CMOL circuits have another advantage in comparison with regular CMOS circuits and are inherently defect tolerant [12], [13]. We have recently shown that basic modules of Rijndael can be implemented by CMOL technology with very interesting results [16]. The results we have obtained demonstrate that longer keys can be easily realized by CMOL, making unauthorized deciphering almost impossible.…”
Section: Introductionmentioning
confidence: 89%